2012
DOI: 10.1002/jso.23060
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up after primary treatment of soft tissue sarcoma of extremities: Impact of frequency of follow‐up imaging on disease‐specific survival

Abstract: More frequent follow-up were associated with improved survival in high-risk relapsing patients with extremity STS by providing greater opportunities for adequate reoperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 22 publications
0
24
0
8
Order By: Relevance
“…A retrospective analysis on a cohort of 80 relapsing patients after primary treatment for an extremity soft tissue sarcoma by Chou et al [4] showed no difference in time to detection and the median size of both pulmonary metastasis and local recurrences detected based on the frequency of followup visits. Although they did suggest that more frequent followup was associated with improved survival after treatment for relapse in patients with high-risk features, they failed to define objective followup intervals and patients in their study had varying followup intervals based on physicians' preferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective analysis on a cohort of 80 relapsing patients after primary treatment for an extremity soft tissue sarcoma by Chou et al [4] showed no difference in time to detection and the median size of both pulmonary metastasis and local recurrences detected based on the frequency of followup visits. Although they did suggest that more frequent followup was associated with improved survival after treatment for relapse in patients with high-risk features, they failed to define objective followup intervals and patients in their study had varying followup intervals based on physicians' preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade sarcomas have little metastatic potential [13] and tumor-related mortality; hence, retrospective studies suggest that surveillance is likely to have a positive impact only in highrisk cases [4]. TOSS included all sarcomas without risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work suggests that, if detected early, such disease may be more easily treatable and, in some cases, even curable with complete metastasectomy [1,2]. Some studies conclude that more aggressive pulmonary screening may facilitate earlier detection of lung metastases and improve survival for soft tissue sarcoma, particularly for higher risk patients [5,6]; others, however, either failed to confirm this advantage or demonstrated that less frequent scans are more appropriate for lower risk patients [13,17,20]. Although the optimal imaging frequency and modality to maximize survival remain unknown, it is generally agreed that patients with sarcoma require some form of surveillance that should be designed to maximize the number of recurrences detected per examination performed; therefore, understanding the frequency and timing of these events is necessary to determine optimal followup schedules.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that after treatment of primary STS the disease recurs in approximately 40–60 % of patients [14], depending on histological grade and subtype of sarcoma, tumor size, and type of local treatment. The majority of recurrences (approximately 80 %) occur within the first 3 years of observation.…”
Section: Pattern Of Recurrence In Soft Tissue Sarcomas (Sts)mentioning
confidence: 99%
“…Regular H&P (history and physical examination) with a chest X-ray permit detection of more than half of cases with asymptomatic lung metastases [1, 4, 7]. It is also estimated that lung metastasectomies enable long-term survival in 30–40 % of cases [6, 8, 9].…”
Section: Benefits Of Follow-upmentioning
confidence: 99%